Public policy support and the competitiveness of the renewable energy sector – The case of Poland. (October 2021) - Jankowska, Barbara; Staliński, Adam; Trąpczyński, Piotr
Abstract: Many countries worldwide developed own policies of fostering the sector of renewable energy technologies (RET). Indeed, public policy support has been discussed as pivotal to facilitating new sectors within the theory of infant industries. Particularly in the context of emerging economies, the achievement of the international competitiveness of the RET sector may require public support. On the other hand, however, certain governmental decisions may not turn out to be supportive to RET companies, particularly at such early stage. Thus, the objective of this paper is to explore the role of public support in the RET sector in the context of an emerging market of Poland. In particular, the study aims at investigating the importance of different types of support measures, as well as their relative relevance in different sub-sectors of RET. The study addresses these objectives in a mixed-method empirical study, which sheds light on both the particular support instruments, as well as the expectations of RET companies with regard to the role of the public authorities in building the competitiveness of this sector. Among others, the study finds support for the notion that economic policy is a key determinant of the competitive position of the RET sector, whereby hard measures have a stronger influence than soft ones. The conclusion section provides a number of policy recommendation. Highlights: Economic policy is the key determinant of the competitive position of subsectors of RET. Administrative simplifications are required to shorten the period of preparing investments and related costs. Long-term research on the strength and direction of wind as well as water flow in rivers should be initiated in Poland. The government should conduct intensive social campaigns which would provide people with basic knowledge on RET.